2023
DOI: 10.1039/d2sc05324a
|View full text |Cite
|
Sign up to set email alerts
|

Closing the green gap of photosystem I with synthetic fluorophores for enhanced photocurrent generation in photobiocathodes

Abstract: Dyes are covalently bound to photosystem I to close its green gap, and the constructs' photocurrent densities on 3D ITO are determined in direct and mediated electron transfer. Photocurrent generation is enhanced by the presence of fluorophores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…70–78 Regarding the PE current density of this system, the highest PE current density among recent studies was achieved in this work as shown in Fig. S7 † 10–14,29–33,79–84.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…70–78 Regarding the PE current density of this system, the highest PE current density among recent studies was achieved in this work as shown in Fig. S7 † 10–14,29–33,79–84.…”
Section: Discussionsupporting
confidence: 51%
“…S7. † [10][11][12][13][14][29][30][31][32][33][79][80][81][82][83][84] For efficient collection of PEs from TMs, TMs need to be attached and electrically connected to a 3D printed graphene electrode. However, since TMs have abundant ionized side groups, they do not form stable bonds with graphene electrodes that are hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
“…Between the Q y and Q x bands of BChl, a less absorptive window of wavelength exists in the range of 620–750 nm. Recent studies have demonstrated that external fluorophores (fluorescent dyes and quantum dots) enhance absorption cross sections of reconstituted LH1 (B820- and B875-type) , and LHCII from spinach and increase the charge-separation capacity of RC complexes. More recently, we reported that artificial fluorophores, whose absorption bands complement the less absorptive window, act as extrinsic LH chromophores that expand the LH window when the fluorophores are covalently attached to LH2 (LH2-Fluor) or LH1-RC (LH1-RC-Fluor) . Femtosecond absorption spectroscopy revealed that the time constants of EET from the attached fluorophores to BChls in these biohybrid LH complexes are in the time range of subpicoseconds to 23 ps, which are comparable to that of native EET systems. In addition, the absorbed light energy by the fluorophores leads to the charge separation and drives the photocatalytic reaction of the RC, resulting in photocurrent generation when LH1-RC-Fluor or LH2-Fluor/LH1-RC are reconstituted into a lipid bilayer and assembled on an indium–tin-oxide (ITO) electrode. , …”
Section: Introductionmentioning
confidence: 98%
“…Many artificial and biohybrid LH systems have been reported. Although it is known that the functional coupling of an LH system and a photocatalytic component is essential for harnessing solar energy, , a quantitative evaluation of how effectively the excitation energy absorbed by the external LH chromophores leads to photochemical reactions has not been addressed. Such evaluation methods are necessary for the development of solar-to-energy conversion systems.…”
Section: Introductionmentioning
confidence: 99%
“…Natural light-harvesting complexes, such as the photosystem (PS), have drawn some attention in this direction because of their natural function in producing energy upon light excitation. Previous studies revealed the possibility of generating photocurrents using the PS protein and of utilizing the protein in photovoltaic devices , and solar cells. The use of the PS protein in such devices requires a deposition process of the PS, resulting in a monolayer or a multilayer film, and thus, it has to be formed on a surface, such as an electrode or gold nanoparticle . Furthermore, in most studies, the photocurrent generation was achieved in an electrochemical setup, i.e., in an aqueous solution, which can be a limiting factor.…”
Section: Introductionmentioning
confidence: 99%